Analysis of the Effect Of Profitability of Asset Structure Asset Growth on Debt Policy in Health Companies Listed on the Indonesia Stock Exchange - Pricillia Deborah Valentine; Nayla Nurul Putri; Nuraini Azlin; Indah Lestari; Meigia Nidya Sari (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the influence of profitability, asset structure, and asset growth on debt policy in health sector companies listed on the Indonesia Stock Exchange. The data used is secondary data from the financial statements of 45 companies. After the normality analysis, the data showed a normal distribution with an estimated skew of 0.067 (more than 0.05). With an F value of 12.827 and a p-value of 0.000, the results of the simultaneous test (F Test) show that the integrated independent variables significantly affect the debt policy. However, according to a partial analysis (T-Test), the only factor that has a significant negative influence on debt policy is profitability (p-value = 0.000), while asset growth and asset structure do not show a significant influence.